Anterior-posterior ground reaction forces across a range of running speeds in unilateral transfemoral amputees - Sakata, H.; Hashizume, S.; Amma, R.; Hisano, G.; Murata, H.; Takemura, H.; Usui, F.; Hobara, H. (Sports Biomechanics, 2024)
As a fundamental motor pattern, the ability to run at a range of constant speeds is a prerequisite for participating in competitive games and recreational sports. However, it remains unclear how unilateral transfemoral amputees modulate anterior and posterior ground reaction force impulses (GRFIs) in order to maintain constant running speeds. The purpose of this study was to investigate anterior and posterior GRFIs across a wide range of constant running speeds in unilateral transfemoral amputees wearing a running-specific prosthesis. Eleven runners with unilateral transfemoral amputation ran on an instrumented treadmill at 5 different speeds (30%, 40%, 50%, 60%, and 70% of the average velocity of their 100-m personal records). Anterior-posterior ground reaction forces (GRFs) were measured at 1000 Hz over 14 consecutive steps. Impulse, magnitude, and duration of anterior and posterior GRFs were compared between the affected and unaffected limbs at each speed. The net anterior-posterior GRFI, reflecting the changes in horizontal running velocity, was consistently positive (propulsion) in the affected limb and negative (braking) in the unaffected limb at all speeds. Regardless of running speed, unilateral transfemoral amputees maintain constant running speeds not over each step, but over 2 consecutive steps (i.e., one stride).